Effects of Dietary Soy Sauce Dregs and Cassava Peel Meal on the Performance of Production and Reproduction of Grower Quails (Cortunix cortunix Japonica) - Ummah, Muhammad Misbahul; Rojabi, Wahib Moh.Ridho; Hertamawati, Rosa Tri (Universitas Airlangga, 2024)
Background: The cost of feed is a significant factor in the viability of a quail farming business. Purpose: This study aims to determine the effects of dietary soy sauce dregs and cassava peel meal on the performance production and reproduction of grower quails (Cortunix cortunix Japonica). Methods: This study employed four treatment groups, each with five replicates, namely P0 (control), P1 (5%), P2 (10%), and P3 (15%). The parameters observed were feed consumption, body weight gain, feed conversion ratio, mortality, body weight at sexual maturity, egg weight, and laying age. Data analysis was conducted using the analysis of variance (ANOVA) test, followed by the Duncan's multiple range test (DMRT) to identify any significant differences. Results: The results showed that the addition of soy sauce dregs and cassava peel meal to the feed up to 15% to the treatment group resulted in significant effects (p < 0.05) on feed consumption, egg weight, and laying age. However, it had no significant effect on body weight, feed conversion ratio, mortality, and body weight at sexual maturity. Conclusion: The supplementation of soy sauce dregs and cassava peel meal up to 15% in grower quail diets resulted in improvements in the performance of both production and reproduction of grower quails, as evidenced by increased feed consumption, egg weight, and laying age.